Letter - Squance, W. J. R.
010-0155-001 Telegraphic Address. 'Aslocobrom, Haver, London." Telephone no Hampstead 6300 When replying refer to S.1/830 Associated Society of Locomotive Engineers and Firemen. TRADE UNION No. 348 T. APPROVED SOCIETY No. 253 9, Arkwright Road, Hampstead, London, N.W.3. W.J.R.Squance GENERAL SECRETARY. W.P. Allen ASSISTANT GENERAL SECRETARY NOTE. For each subject-a separate letter. Sir W.M. Citrine, K.B.E., General Secretary, T.U.C. General Council, Transport House, Smith Square, LONDON, S.W.1. DMS. 31st July, 1936. Dear Sir Walter, We have received correspondence from the International Transportworkers' Federation regarding the Spanish workers' struggle against Fascism, and requesting us to keep a watchful eye on the export of war material, etc., to the forces of reaction in Spain. My Executive Committee have given very careful consideration to the circular, and whilst they appreciate the sentiments expressed therein and are prepared to render all possible assistance, they are not unmindful of the difficulties to be surmounted to carry such a policy into effect. They are, therefore, of the opinion that the question is one that could be more effectively dealt with by the T.U.C., and they have requested me to advise you accordingly. Should, therefore, the T.U.C. deal with this matter, I shall be obliged to have their decision thereon. Yours faithfully, W.J.R. Squance GENERAL SECRETARY. 292/946/10/168